Training of Cash Waqf Management on Da'i and Mubaligh - Achmad Soediro; Media Kusumawardani; Muhammad Farhan; Fardinant Adhitama; Hasni Yusrianti; Patmawati Patmawati; Anton Indra Budiman (Faculty of Economics, Universitas Sriwijaya, 2022)
Community Service Implementation Activities with the theme